2018
DOI: 10.1007/s00109-018-1638-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte transplantation and advancements in alternative cell sources for liver-based regenerative medicine

Abstract: Human hepatocyte transplantation has been actively perused as an alternative to liver replacement for acute liver failure and liver-based metabolic defects. Current challenges in this field include a limited cell source, reduced cell viability following cryopreservation and poor engraftment of cells into the recipient liver with consequent limited life span. As a result, alternative stem cell sources such as pluripotent stem cells, fibroblasts, hepatic progenitor cells, amniotic epithelial cells and mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 88 publications
0
50
0
Order By: Relevance
“…Our study demonstrated cGMP‐derived hepatic constructs remained viable, and more importantly, functional within the peritoneal cavity of fully immune competent C57BL/6 and CD‐1 mice for a time period long enough to result in recovery from ALF if used in patients. This in turn strongly advocates for further development of hPSC‐hepatocytes as a clinical therapeutic .…”
Section: Discussionmentioning
confidence: 98%
“…Our study demonstrated cGMP‐derived hepatic constructs remained viable, and more importantly, functional within the peritoneal cavity of fully immune competent C57BL/6 and CD‐1 mice for a time period long enough to result in recovery from ALF if used in patients. This in turn strongly advocates for further development of hPSC‐hepatocytes as a clinical therapeutic .…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, one of the main indications for human hepatocyte transplantation therapy is ALF 125,126 ; human hepatocyte transplantation has been actively perused as an alternative to liver replacement for ALF. 127 In this regard, 37 patients with ALF have been treated with human hepatocytes for drug-induced, viral, and obscure ALF. Ten of these patients received intraportal hepatocyte infusions, with 2 making a full recovery without the requirement of OLT, and 3 were successfully bridged to transplantation.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…However, present challenges include a reduced cell source, decreased cell viability following cryopreservation, and poor engraftment of cells into the recipient liver with consequently a limited lifespan. 127,133,134 Therefore, alternative stem cell sources including pluripotent stem cells, fibroblasts, hepatic progenitor cells, amniotic epithelial cells, and mesenchymal stem/stromal cells can be introduced to generate induced hepatocyte-like cells, with each technique exhibiting advantages and disadvantages. Mesenchymal stem/stromal cells transplantation had beneficial effects, especially in ACLF patients.…”
Section: Novel Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several issues complicated the feasibility and safety of liver transplantation in the clinical practice, including shortage of donor livers, the quality of cryopreserved cells, the need for invasive procedures to perform portal infusions, limited space in the native liver, the risk of extra-hepatic spread of transplanted hepatocytes (mostly to the lung), limited engraftment of transplanted cells and the need of immunosuppression to prevent rejection. These limitations led to an increased interest in the potential use of stem cells with hepatic differentiation capability [10].…”
Section: Introductionmentioning
confidence: 99%